Lusaka´s urban healers: negotiators of modernity, Christianity and local cultural traditions - Mildnerova, Katerina (2011)
The syncretic character of contemporary Lusaka´s medical culture encompassing the elements of traditional and Christian healing as well as western biomedicine has been significantly shaped by the processes of modernization, and now globalization. The circulation of persons, objects and ideas, typical for the process of globalization, is thus reflected in African contemporary healing. The healers – social and health experts – represent creative and experimental figures whose eclectic skills are involved in the process of ‘bricolage’. Since their authority and legitimacy is threatened by many competitors in the city, it must be constantly reaffirmed and negotiated by introducing innovations .In the act of crossing social, geographical and ideological borders, the healers themselves participate in the reproduction and construction of the borders themselves. At the same time they transcend the bounds of locality and tradition and act on the broader social scale through engagement in different institutions such as healers’ associations, prophet-healing churches, cults of affliction, and organs of the state.